INVESTMENT BEHAVIOUR TOWARDS COMMODITY MARKET - Dhinakar, Dr.A.Jelince; Jeevanandham, P. (IJRDO - Journal of Business Management, 2018)
This study analyses the Indian Agricultural Commodity Markets. In an agricultural country like India, the price of agricultural commodities, especially of food grains hold a key position in the price structure of the country. The commodity market in India has witnessed a phenomenal growth. The futures trading have ecosystem linkages which results in employment generation process. Commodity markets have a crucial role in developing agriculture dominated economies. Commodity markets have a significant role in the price risk management process especially in case of India being an agricultural dominated economy. The influence between the investor’s overall satisfaction with various aspects underlying commodity trading such as Category search before making investment decision, Information search before making investment decision, technical analysis and fundamental analysis towards commodity market have also been studied. A Sample of 323 respondents is taken for this study.